'Menunggu Godot' Peradilan HAM dan Tanggung Jawab TNI - Eko Prasetyo (Unisia, 2002)
The emerging of Human Rights Court particularly for the Indonesian National Army, the myths regarding patriotic and war should be disarmed and the responsibility should be carried out in this context, the norm of human right prepares an effective service for those who become the victims of naive nationalism or stability in appearance. Practising of responsibility stated above has large implication, namely choosing the action of security must consider four important factors: (1) whether the action aforementioned is in accordance with law, (2) is it proportionally?, (3) is it coincide with the ethics ?, and (4) that the action is really needed and accepted by society. According to writer that described four considerations must be guidance, instead, it needed to be organization formulation so that they do not motivate the Indonesian National Army return to dark eras.